2015
DOI: 10.1007/s00228-015-1998-5
|View full text |Cite
|
Sign up to set email alerts
|

First-line therapy for non-transplant eligible patients with multiple myeloma: direct and adjusted indirect comparison of treatment regimens on the existing market in Germany

Abstract: VMP and MPT seem more effective than MP, VMP was superior to MPT regarding response criteria and AEs. Our results may best be confirmed by a head-to-head trial of VMP vs. MPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Their results, however, showed that there was no difference in PFS between maintenance and no-maintenance approaches. 42 Therefore, we believe that it is appropriate to combine these trials, as performed previously, 11,43 and the results of our sensitivity analysis confirm this assumption (see Online Supplementary Appendix 7 ).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Their results, however, showed that there was no difference in PFS between maintenance and no-maintenance approaches. 42 Therefore, we believe that it is appropriate to combine these trials, as performed previously, 11,43 and the results of our sensitivity analysis confirm this assumption (see Online Supplementary Appendix 7 ).…”
Section: Discussionsupporting
confidence: 79%
“…Our results align with the results from Kuhr et al . 11 in that VMP and MPT are more effective than MP. Our results also confirm the conclusion from Weisel et al .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The next step forward in the treatment armamentarium was the use of high-dose mephalan followed by autologous stem cell transplant in young patients, with mephalan-prednisolone remaining the standard of care in the elderly 8. Significant developments have occurred in recent years with the availability of novel agents including arsenic trioxide and farnesyltransferase inhibitor 2-methoxyestradiol 9. Over the past decade, with the introduction of immune-modulating drugs such as thalidomide, lenalidomide, pamlidomide and protease inhibitors such as bortezomib and carfilzomib, the treatment of myeloma has been transformed.…”
Section: Discussionmentioning
confidence: 99%